1989
DOI: 10.1021/bi00439a019
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stabilities of globular proteins

Abstract: Statistical thermodynamic theory has recently been developed to account for the stabilities of globular proteins. Here we extend that work to predict the dependence on temperature. Folding is assumed to be driven by solvophobic interactions and opposed by the conformational entropy. The temperature dependence of the solvophobic interaction is taken from the transfer experiments on amino acids by Tanford and Nozaki and on model solutes by Gill and Wadsö. One long-standing puzzle has been why proteins denature u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
175
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(183 citation statements)
references
References 31 publications
8
175
0
Order By: Relevance
“…Then, different volumes of the heme-HSA solution (in the absence and presence of the chaotropic agent) were mixed to obtain the desired GnCl concentration at a fixed heme-HSA concentration. GnCl-induced HSA unfolding is fully reversible under the experimental conditions reported in the present study [25][26][27][28][29][30][31][32]. Samples were incubated for 1 h before measurements.…”
Section: Methodsmentioning
confidence: 62%
See 1 more Smart Citation
“…Then, different volumes of the heme-HSA solution (in the absence and presence of the chaotropic agent) were mixed to obtain the desired GnCl concentration at a fixed heme-HSA concentration. GnCl-induced HSA unfolding is fully reversible under the experimental conditions reported in the present study [25][26][27][28][29][30][31][32]. Samples were incubated for 1 h before measurements.…”
Section: Methodsmentioning
confidence: 62%
“…The multidomain structural organization makes HSA a model system to investigate how interdomain interactions could affect the folding/unfolding process [25][26][27][28][29][30][31][32]. With use of different experimental techniques to follow thermal or chaotropic denaturation of HSA, it has been observed that the HSA N state unfolds in two sequential steps, domain II unfolding before domain I (i.e., the heme binding domain) [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Iron(III) heme is secured to HSA by the long IA-IB connecting loop that fits into the cleft opening [14-16, 29, 33, 34]. In turn, heme endows HSA with globin-like reactivity [4,[35][36][37][38][39] and spectroscopic properties [22, 30-32, 34, 40-43]. [14] HSA is crucial for heme scavenging, providing protection against free heme oxidative damage, limiting the access of pathogens to heme, and contributing to iron homeostasis by recycling the heme iron.…”
Section: Introductionmentioning
confidence: 99%
“…We estimate that at 1°C on average six of the 12 peptide bonds are in folded conformations (predominantly 3 10 -and π-helix), while the other six are in unfolded ( -turn/PPII) conformations. The folded and unfolded populations do not change significantly as the temperature is increased from 1 to 60°C, suggesting a unique energy landscape where the folded and unfolded conformations are essentially degenerate in energy and exhibit identical temperature dependences.An understanding of the mechanisms of protein folding will enable the de novo design of proteins with profound commercial and medical applications (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Over the past 50 years, significant effort to elucidate protein folding and unfolding mechanisms has been expended.…”
mentioning
confidence: 99%